2015
DOI: 10.1039/c5cc08421k
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing supramolecular heterometallic gels based on the synergistic effect of the constituent metal ions

Abstract: Supramolecular heterometallic gels with synergistic properties were prepared for the first time using ligand with Co(2+) and Ni(2+), and their macroscopic self-healing has been achieved by improving the unfavorable viscoelasticity of each monometallic gel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…24 The preparation of bulk self-healable gels through noncovalent interactions without the use of "polymers'' remains challenging due to their intrinsic viscoelasticity. 27 15 are not included here. Detailed studies on the underlying self-healing mechanisms of different gels have been previously reviewed.…”
Section: Self-healing Gelsmentioning
confidence: 99%
“…24 The preparation of bulk self-healable gels through noncovalent interactions without the use of "polymers'' remains challenging due to their intrinsic viscoelasticity. 27 15 are not included here. Detailed studies on the underlying self-healing mechanisms of different gels have been previously reviewed.…”
Section: Self-healing Gelsmentioning
confidence: 99%
“…23a). 105 When a DMF solution of L15 was mixed with a DMF solution of NiCl 2 Á6H 2 O or CoCl 2 Á6H 2 O at room temperature, the mixture spontaneously formed monometallic CPGs, L15-Ni and L15-Co, respectively. They explained that the cooperative hydrogen bonding interaction of the NH group of L15 played an important role in gelation.…”
Section: Self-healing In Cpgsmentioning
confidence: 99%
“…35,36 Yan et al reported a self-healing supramolecular heterometallic MOG based on Co 2+ and Ni 2+ ions exhibiting the synergistic effect of the constituent metal ions. 37 Di ́az et al fabricated a Cu 2+ -based self-healing MOG, which showed proton conducting properties. 38 Yu and coworkers reported a self-healing hybrid gel based on Zn-tpy and polypyrrole, which showed conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The self-healing properties of MOGs are governed by various interactions, such as reversible coulombic interactions, molecular recognitions, hydrogen bonding, hydrophobic interactions, and metal–ligand coordination. Quite a few reports of MOGs exhibiting self-healing property have been reported in literature. , Yan et al reported a self-healing supramolecular heterometallic MOG based on Co 2+ and Ni 2+ ions exhibiting the synergistic effect of the constituent metal ions . Díaz et al fabricated a Cu 2+ -based self-healing MOG, which showed proton conducting properties .…”
Section: Introductionmentioning
confidence: 99%